Packet loss-ratio based scheduler: an adaptive scheduling scheme to increase the number of multimedia applications in WLAN. (18th February 2011) - Jibukumar, M.G.; Datta, Raja; Biswas, Prabir K.
The reference scheduler in IEEE 802.11e fails to maintain the goal of quality of service (QoS) support and high network efficiency simultaneously. In this paper we investigate channel access schemes to increase the number of multimedia applications in wireless local area network (WLAN) while maintaining the QoS requirements. We have developed a scheduling scheme, named as packet loss-ratio based scheduler (PLS) that takes into account the packet losses occurred while allotting the transmission time to a multimedia stream. To implement this scheme the access point (AP) requires only the queue size information and can be implemented within the format of IEEE 802.11e. The simulation results show that the PLS can accommodate more number of traffic streams and can also randomise the packet loss from a traffic stream, which is a requirement for multimedia coder-decoders (CODECs) to conceal the distortion.